Moral Nimby-ism? Understanding Societal Support for Monetary Compensation to Plasma Donors in Canada - Nicola Lacetera; Mario Macis (Center for Economic Studies and ifo Institute (CESifo), 2018)
The growing demand for plasma, especially for the manufacture of therapeutic products, creates an urgent need for a careful discussion on the relative merits of different procurement and allocation systems in a way that addresses the increasing demand while abiding by the prevailing moral values in a society. We conducted a randomized survey experiment with a representative sample of 826 Canadian residents to assess attitudes toward legalizing the compensation to plasma donors, a practice that is illegal in several Canadian provinces. We found no evidence of widespread societal opposition to payments to plasma donors, because over 70% of respondents reported that they would support compensation. The support was higher for paying plasma donors in Australia and the United States than in Canada, but the differences were small, suggesting a weak role for “moral NIMBY-ism” or moral relativism in explaining the findings. Moral concerns were the highest-rated reason that respondents gave for being against payment, together with concerns for the safety of plasma supplied by compensated donors, although most of the plasma in Canada does come from compensated American donors. Among those in favor of legalizing compensation for donors (in Canada as well as in Australia), the highest-rated motive was to guarantee a higher domestic supply. Finally, roughly half of those who declared to be against payments reported that they would reconsider their position if the domestic supply and imports were insufficient to meet domestic demand. Most Canadians, therefore, seem to espouse a consequentialist view to issues related to the procurement of plasma.
Keywords: C93; H44; I18; K00; Z10; 330; ethics; repugnant markets; health; plasma